Photometric Observations of Short Period Variable Stars: EH Librae - Djumari, Sulthan Julieri; Malasan, Hakim Luthfi; Wibowo, Ridlo Wahyudi; Wahidin, Alka Budi (Lambung Mangkurat University Press, 2024)
EH Librae [BD-00 2911; αJ2000 = 14h58m55.92s; δJ2000 = -0°56'53.01'] is a pulsating variable δ Scuti stars which is located in the constellation of Libra and has a period of 0.0884129 days. The aim of this research is to obtain and analyze the light curve, deduce the period, and derive the physical parameters of EH Librae. Observations were made using the ITERA Robotic Telescope 0.25m Ritchey-Cretian with CCD ATIK 383L+ on the BVR band. Aperture photometry was performed to measure the flux of EH Librae. Light curve was constructed using the differential photometry method, and the determination of the period was carried out using the Lomb – Scargle method. Secondary data from the Transiting Exoplanet Survey Satellite (TESS) is used as an addition to derive the physical parameters of EH Librae. The results of this study are the light curve of EH Librae on the BVR band with Magnitude, V = 9.506 – 10.071 ± 0.002. Using the index color = 0.271, we derived the = (7.7 ± 0.4) 103 K. O – C diagram shows no significant changes in the period. Derivation of physical parameters are = 2.12 ; = 1.4 ; and = 3.93 cgs was carried out using asteroseismology method with = 846 and = 51.9